A conditioning-free magnesium chloride complex electrolyte for rechargeable magnesium batteries. Issue 19 (21st April 2016) - Ha, Jung Hoon; Adams, Brian; Cho, Jae-Hyun; Duffort, Victor; Kim, Jong Hak; Chung, Kyung Yoon; Cho, Byung Won; Nazar, Linda F.; Oh, Si Hyoung
Abstract : Catalytic dissolution of Mg metal in THF leads to a highly stable electrolyte for rechargeable magnesium batteries which share many common features with MACC, but does not require an onerous conditioning process. The high Mg to Al ratio in the electrolyte promotes 100% coulombic efficiency for Mg in the first cycle. Abstract : The dissolution of Mg metal in AlCl3 /THF using CrCl3 as a "promoter" yields a magnesium aluminum chloride complex electrolyte which shares many common features with MACC, but does not require an onerous conditioning process. This crucial advantage originates from the very high Mg to Al ratio in the new electrolyte, "MaCC", which promotes 100% coulombic efficiency for Mg in the first cycle.